PENGARUH PENDIDIKAN DALAM KELUARGA TERHADAP MOTIVASI BELAJAR SISWA KELAS V DI MI ABNAUL WATHON KABUPATEN CIREBON - Masud, Maftukhah Tukha (UIN Siber Syekh Nurjati Cirebon, 2022)
This research is a quantitative research using associative design. Data collection techniques in this study used a questionnaire and documentation. The samples used were 28 students of class V MI Abnaul Wathon Cirebon Regency and 28 guardians of students. Based on the analysis, it can be said (1) Judging from the questionnaire recapitulation using the Guttman scale, the average percentage of education in the family is 61% and is considered sufficient. In this case, of course, education in the family is very influential for the growth and development of children, including their learning motivation. (2) Through a questionnaire, it can be seen that the learning motivation of fifth grade students at MI Abnaul Wathon, Cirebon Regency is 82% and is considered very good. (3) Based on the linear test obtained the value of sig. of 0.860 > 0.05, it can be said that there is a linear relationship between the education variable in the family (X) and the student's learning motivation variable (Y) class V MI Abnaul Wathon Cirebon Regency